Kesehatan Mental Kadet Maritim di Era Digital: Studi Netnografi Instagram dalam Konteks Amandemen BST- STCW 2026 - Rosmawati; Oktavera Sulistiana; Feronika Sekar Puriningsih; Ludfi Pratiwi Bowo; Henny Pasandang Nari (PIP Makassar, 2026)
This study aims to analyse the mental health needs and patterns of psychosocial support among maritime cadets in the digital era, particularly in anticipation of the 2026 amendment to the Standards of Training, Certification and Watchkeeping (STCW). A qualitative Netnographic approach was employed to analyse public Instagram content related to maritime cadets. Data were collected from 20 digital postings and processed using NVivo thematic coding analysis.The findings indicate that the dominant narrative within the digital ecosystem of maritime cadets is “appreciation and positive support,” representing 70% of all coded narratives. Notably, 68.6% of these supportive narratives originate from general internet users, suggesting that emotional validation is largely derived from public digital audiences. In contrast, narratives coded under “struggle” account for only 1.3% of total mentions, indicating possible impression management in social media environments.Digital support functions as a proxy protective factor against psychological pressure. However, the dominance of image-based validation may create a gap between public perception and actual psychological experiences. This study contributes to maritime mental health literature by positioning digital social support as a critical mediating variable and recommends that maritime institutions integrate authentic mental health support programs in preparation for upcoming STCW standards.